MARKED ECOLOGICAL SHIFTS DURING 6.2-2.4 MA REVEALED BY A TERRESTRIAL MOLLUSCAN RECORD FROM THE CHINESE RED CLAY FORMATION AND IMPLICATION FOR PALAEOCLIMATIC EVOLUTION - Wu N.; Pei Y.; Lu H.; Guo Z.; Li F.; Liu T. (My University, 2006)
A new molluscan fossil record from the late Miocene-Pliocene Xifeng Red Clay sequence in the central Loess Plateau, northern China, reveals the process of ecological environmental changes during ~ 6.2-2.4 Ma. Three marked ecological shifts in mollusk assemblages occurred at about 5.4, 4.5, and 3.4 Ma, which reflect changes in the East Asian monsoon circulation. A predominantly cold-aridiphilous group reveals an extremely cold dry climate due to strengthened East Asian winter monsoon during ~ 6.2-5.4 Ma. A predominantly thermo-humidiphilous group from ~ 5.4-4.5 Ma indicates a strengthening of the East Asia summer monsoon circulation. The marked occurrence of meso-xerophilous taxa during ~ 4.5-3.4 Ma implies mild climatic conditions. From 3.4 Ma, the cold-aridiphilious species again became dominant in the fossil assemblages, indicating that the winter monsoon was gradually intensifying towards the Quaternary glaciations. Climate changes in this region were characterized by stepwise cooling from 5.4 to 2.4 Ma with a 1 Ma rhythmicity. The cooling trend is in good agreement with the general global cooling trend during this period, as documented by marine δ18O records. The formation and development of the Northern Hemisphere ice sheets during the late Pliocene accelerated the climate deterioration towards the Quaternary glaciations. The history of environmental changes revealed by the Red Clay molluscan fossils is coupled in phase with the process of Tibetan Plateau uplift, which may be the major cause and forcing mechanism of late Miocene-Pliocene environmental changes in the Loess Plateau. © 2005 Elsevier B.V. All rights reserved.
Keywords: LATE MIOCENE-PLIOCENE; MOLLUSK GROUPS; PALAEOCLIMATIC EVOLUTION; RED CLAY; Quaternary; Pliocene; Miocene; Cenozoic::Quaternary; Кайнозой::Четвертичная; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен